DNA repair and cancer in colon and rectum: Novel players in genetic susceptibility - Pardini, Barbara; Corrado, Alda; Paolicchi, Elisa; Cugliari, Giovanni; Berndt, Sonja I; Bezieau, Stephane; Bien, Stephanie A; Brenner, Hermann; Caan, Bette J; Campbell, Peter T; Casey, Graham; Chan, Andrew T; et al. (International journal of cancer, 2020)
Interindividual differences in DNA repair systems may play a role in modulating the individual risk of developing colorectal cancer. To better ascertain the role of DNA repair gene polymorphisms on colon and rectal cancer risk individually, we evaluated 15,419 single nucleotide polymorphisms (SNPs) within 185 DNA repair genes using GWAS data from the Colon Cancer Family Registry (CCFR) and the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO), which included 8,178 colon cancer, 2,936 rectum cancer cases and 14,659 controls. Rs1800734 (in MLH1 gene) was associated with colon cancer risk (p-value = 3.5 × 10-6 ) and rs2189517 (in RAD51B) with rectal cancer risk (p-value = 5.7 × 10-6 ). The results had statistical significance close to the Bonferroni corrected p-value of 5.8 × 10-6 . Ninety-four SNPs were significantly associated with colorectal cancer risk after Binomial Sequential Goodness of Fit (BSGoF) procedure and confirmed the relevance of DNA mismatch repair (MMR) and homologous recombination pathways for colon and rectum cancer, respectively. Defects in MMR genes are known to be crucial for familial form of colorectal cancer but our findings suggest that specific genetic variations in MLH1 are important also in the individual predisposition to sporadic colon cancer. Other SNPs associated with the risk of colon cancer (e.g., rs16906252 in MGMT) were found to affect mRNA expression levels in colon transverse and therefore working as possible cis-eQTL suggesting possible mechanisms of carcinogenesis.
Keywords: DNA vazebné proteiny; oprava DNA; dospělí; DNA modifikační methylasy; kolon; hodnocení rizik; Female; Adult; ženské pohlaví; mladý dospělý; jednonukleotidový polymorfismus; nádorové supresorové proteiny; Registries; MutL Protein Homolog 1; nádory tračníku; Colon; Rectum; lidé; nádory rekta; Rectal Neoplasms; Polymorphism, Single Nucleotide; biologická variabilita populace; genetická predispozice k nemoci; studie případů a kontrol; enzymy opravy DNA; Biological Variation, Population; Carcinogenesis; DNA Repair; Genetic Predisposition to Disease; Risk Assessment; DNA Repair Enzymes; karcinogeneze; Colonic Neoplasms; Humans; MutL homolog 1; Male; Tumor Suppressor Proteins; Case-Control Studies; Aged; Young Adult; DNA-Binding Proteins; lidé středního věku; registrace; senioři; mužské pohlaví; rektum; Middle Aged; DNA Modification Methylases